Effect of Class Size on Quality of Education in Public Secondary Schools in Temeke Municipality, Tanzania - Rachel Kalonga; Prospery M. Mwila (PT. Pusmedia Group Indonesia, 2025)
This study aimed to investigate the effect of class size on the quality of education in secondary schools in Temeke Municipality, Tanzania. Using a mixed-methods approach with a convergent design, data were collected from a diverse sample comprising 225 students, 48 teachers, one district education officer, and heads of schools. Participants were selected using purposive, stratified, and simple random sampling methods.The study employed both qualitative and quantitative approaches, utilizing questionnaires and a semi-structured interview schedule as data collection instruments. Findings revealed that class sizes in secondary schools within Temeke Municipality were notably large, presenting significant challenges for both teachers and students. Teachers expressed concerns about their ability to engage effectively with each student, provide personalized attention, and manage classroom activities in such settings. Specifically, the challenges identified included difficulties in offering individualized support, managing classroom activities, and delivering timely feedback on assignments and tests.The study concluded that efforts are needed to address these challenges posed by large class sizes in Temeke Municipality. Various strategies were proposed to mitigate the problem, including constructing additional classrooms, hiring more teachers, maintaining an optimal teacher-student ratio, ensuring the availability of adequate teaching materials, and providing training for managing large classes.